Inventing Slavonic cultures of writing between Rome and Constantinople - Ivanova, Mirela 1962- (Oxford studies in Byzantium, 2024)
In this meticulously researched study, Mirela Ivanova offers a new critical history of the invention of the Slavonic alphabet. Showing how the alphabet was not invented once, but rather continually contested and redefined in the century following its creation, Ivanova challenges the prevalent nationalist historiography that has built up around it